The role of thrombin in early-onset seizures - Savotchenko, Alina; Klymenko, Mariia; Shypshyna, Mariia; Isaev, Dmytro (Frontiers in Cellular Neuroscience, 2023)
Clinical observations and studies on different animal models of temporal lobe epilepsy (TLE) reveal dysfunction of blood-brain barrier (BBB) during seizures. It accompanies with shifts in ionic composition, imbalance in transmitters and metabolic products, extravasation of blood plasma proteins in the interstitial fluid, causing further abnormal neuronal activity. Among the possible blood components, involved in seizure generation during BBB opening, only thrombin has been shown to produce early-onset seizures. Using the whole-cell recordings from the single hippocampal neurons we recently showed the induction of epileptiform firing activity immediately after addition of thrombin to the blood plasma ionic media. In the present work we mimic some effects of BBB disruption in vitro to examine the effect of modified to blood plasma ACSF on the excitability of hippocampal neurons and the role of serum protein thrombin in the seizure susceptibility. Comparative analysis of model conditions simulating BBB dysfunction was performed using the lithium-pilocarpine model of TLE, which most clearly reflects the BBB disruption in the acute stage. Our results demonstrate the particular role of thrombin in seizure-onset in conditions of BBB disruption.